Morphological, pathogenic and molecular characterization of Lasiodiplodia theobromae: a causal pathogen of black rot disease on kenaf seeds in Malaysia - M., Norhayati; Mohd Hata, Erneeza; Sijam, Kamaruzaman (Friends Science Publishers, 2016)
Kenaf (Hibiscus cannabinus) is a fibre crop grown in Malaysia as a substitute crop for tobacco. Previous study have recorded that kenaf has been infected by various genera of seed-borne pathogen include Fusarium, Synnematium, Alternaria, Colletotrichum and Botrytis. Seed-borne disease affects and actively attacks seeds and may be harmful. Lasiodiplodia theobromae is a seed-borne fungal pathogen that infects a variety of crop seeds. Studies on the isolation of seed-borne fungi on kenaf seed have revealed that L. theobromae causes black rot disease on kenaf seeds. L. theobromae was successfully isolated from kenaf seeds on an agar plate and a blotter. L. theobromae was isolated frequently from infected seeds and identified based on its cultural and morphological characteristics. The fungus sequence was analysed using molecular technique (ITS-rDNA amplification). A pathogenicity test was used to confirm that L. theobromae caused blackening of the seeds and reduced the germination against a control treatment in potato Dextrose Agar (PDA) medium. To our knowledge, this study is the first to confirm that L. theobromae is the causal agent of black rot on kenaf seed in Malaysia.